THE INFLUENCE OF DIGITAL MARKETING COMMUNICATION AND SERVICE QUALITY ON PATIENT DECISIONS IN CHOOSING UKI GENERAL HOSPITAL (RSU) SERVICES: Pengaruh Komunikasi Pemasaran Digital dan Kualitas Pelayanan Terhadap Keputusan Pasien Dalam Memilih Layanan Rumah Sakit Umum (RSU) UKI - Fenny B.N.L Tobing; Rudy Sondang Sinaga; Napoleon Sinaga; Abdiel Putra Bago (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the influence of digital marketing communication and service quality on patient decisions in choosing healthcare services at the UKI General Hospital (RSU UKI), East Jakarta. In the rapidly growing digital era, the public increasingly relies on digital platforms to seek health information before deciding on a medical facility. This research uses a quantitative method with a Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach, involving 100 respondents selected through purposive sampling. The results show that digital marketing communication has a positive and significant impact on patient decision-making. Service quality also plays an essential role, with dimensions such as reliability, responsiveness, assurance, empathy, and tangibles determining patient satisfaction and choice. The combination of effective digital communication strategies and excellent service quality can enhance patient loyalty and strengthen RSU UKI’s reputation. This research offers practical implications for hospital management to optimize digital marketing strategies and continually improve service quality to remain competitive in the healthcare industry.